2006
DOI: 10.1002/mnfr.200600145
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of dietary carotenoids

Abstract: The assessment of carotenoid bioavailability has long been hampered by the limited knowledge of their absorption mechanisms. However, recent reports have elucidated important aspects of carotenoid digestion and absorption. Disruption of food matrix and increasing amounts of fat seem to enhance the absorption of carotenes to a larger extent than that of xanthophylls. Comparing different carotenoid species, xanthophylls seem to be more easily released from the food matrix and more efficiently micellized than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
252
4
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(263 citation statements)
references
References 84 publications
1
252
4
6
Order By: Relevance
“…At the intestinal level, b-carotene absorption is depending on three steps: (1) absorption at the enterocyte brush border membrane level, partly via the cholesterol transporters SR-BI and CD36 [11,71] but also by passive diffusion [83]; (2) enzymatic conversion of a fraction of absorbed b-carotene in a centric or eccentric fashion by the b-carotene 15,15 0 -monooxygenase BCMO1 (releasing retinal) or by the b-carotene 9 0 ,10 0 -dioxygenase, BCDO2 (releasing b-apo-10 0 -carotenal and b-ionone), respectively (Fig. 2, for review see [73].…”
Section: Carotenoid Oxygenasesmentioning
confidence: 99%
“…At the intestinal level, b-carotene absorption is depending on three steps: (1) absorption at the enterocyte brush border membrane level, partly via the cholesterol transporters SR-BI and CD36 [11,71] but also by passive diffusion [83]; (2) enzymatic conversion of a fraction of absorbed b-carotene in a centric or eccentric fashion by the b-carotene 15,15 0 -monooxygenase BCMO1 (releasing retinal) or by the b-carotene 9 0 ,10 0 -dioxygenase, BCDO2 (releasing b-apo-10 0 -carotenal and b-ionone), respectively (Fig. 2, for review see [73].…”
Section: Carotenoid Oxygenasesmentioning
confidence: 99%
“…Humans and animals are not capable of carotenoid biosynthesis, but ingest them as part of their diets. Of the approximately 60 carotenoids present in the human diet, only about 20 have been detected in human blood and tissues (Yonekura and Nagao 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Their non-digestible character in human digestive prevents production of micelles by inhibiting digestive lipases activity and/or by binding to bile acids or to phospholipids. Fibers also increase intestinal content, viscosity and volume thereby slowing processes of diffusion of micelles on the absorbent surface of enterocytes (Yonekura & Nagao, 2007;Eroglu & Harrison, 2013). Besides, Riedl et al (1999) confirmed that dietary fibers decrease carotenoids absorption in human.…”
Section: Discussionmentioning
confidence: 74%
“…These quantities are greater than the minimal quantity of lipids required in a meal (3-5 g) for a good assimilation of carotenoids (Yonekura & Nagao, 2007;Goltz et al, 2012;Hammond & Renzi, 2013).…”
Section: Discussionmentioning
confidence: 89%